The amazing life of birds the twenty-day puberty journal of Duane Homer Leech - Paulsen, Gary 1939-2021 (Wendy Lamb Books, 2006)
As twelve-year-old Duane endures the confusing and humiliating aspects of puberty, he watches a newborn bird in a nest on his windowsill begin to grow and become more independent, all of which he records in his journal